The Causal Effects of Short-Selling Bans: Evidence from Eligibility Thresholds - Crane, Alan D; Crotty, Kevin; Michenaud, Sébastien; Naranjo, Patricia (The Review of Asset Pricing Studies, 2019)
We identify the causal effects of short-selling bans on stock prices using regression discontinuity (RD). We exploit three threshold-based rules that determine a stock’s short-selling eligibility on the Hong Kong Stock Exchange. Short-selling bans have a large effect on short-selling volume at all thresholds. Despite this, bans do not affect stock prices. Stock returns, volatility, and crash risk are not different for banned versus unrestricted stocks when appropriate counterfactual stocks are used to measure a ban’s effects. Our findings suggest that short-selling bans are not as costly as previously argued, but are ineffective at reducing volatility or buttressing prices. Received September 13, 2017; editorial decision April 29, 2018 by Editor Jeffrey Pontiff.